Large-scale international validation of the ADO index in subjects with COPD: an individual subject data analysis of 10 cohorts. Issue 6 (12th December 2012) - Puhan, Milo A; Hansel, Nadia N; Sobradillo, Patricia; Enright, Paul; Lange, Peter; Hickson, DeMarc; Menezes, Ana M; Riet, Gerben ter; Held, Ulrike; Domingo-Salvany, Antonia; Mosenifar, Zab; Antó, Josep M; et al.
Abstract : Background: Little evidence on the validity of simple and widely applicable tools to predict mortality in patients with chronic obstructive pulmonary disease (COPD) exists. Objective: To conduct a large international study to validate the ADO index that uses age, dyspnoea and FEV1 to predict 3-year mortality and to update it in order to make prediction of mortality in COPD patients as generalisable as possible. Design: Individual subject data analysis of 10 European and American cohorts (n=13 914). Setting: Population-based, primary, secondary and tertiary care. Patients: COPD GOLD stages I–IV. Measurements: We validated the original ADO index. We then obtained an updated ADO index in half of our cohorts to improve its predictive accuracy, which in turn was validated comprehensively in the remaining cohorts using discrimination, calibration and decision curve analysis and a number of sensitivity analyses. Results: 1350 (9.7%) of all subjects with COPD (60% male, mean age 61 years, mean FEV1 66% predicted) had died at 3 years. The original ADO index showed high discrimination but poor calibration (p<0.001 for difference between predicted and observed risk). The updated ADO index (scores from 0 to 14) preserved excellent discrimination (area under curve 0.81, 95% CI 0.80 to 0.82) but showed much improved calibration with predicted 3-year risks from 0.7% (95% CI 0.6% to 0.9%, score of 0) to 64.5% (61.2% to 67.7%, score of 14). The ADO index showed higher net benefit in subjects at low-to-moderate risk of 3-year mortality than FEV1 alone. Interpretation: The updated 15-point ADO index accurately predicts 3-year mortality across the COPD severity spectrum and can be used to inform patients about their prognosis, clinical trial study design or benefit harm assessment of medical interventions.